2012
DOI: 10.1177/0891243212451904
|View full text |Cite
|
Sign up to set email alerts
|

Gender Segregation in Elite Academic Science

Abstract: Efforts to understand gender segregation within and among science disciplines have focused on both supply- and demand-side explanations. Yet we know little about how academic scientists themselves view the sources of such segregation. Utilizing data from a survey of scientists at thirty top U.S. graduate programs in physics and biology (n = 2,503) and semistructured interviews with 150 of them, this article examines the reasons academic scientists provide for differences in the distribution of women in biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
146
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 43 publications
4
146
0
3
Order By: Relevance
“…A classic empirical example of confirmation bias showed that peer-reviewers were less favorable toward an essentially identical research manuscript when it was doctored to report results inconsistent with the reviewers' preferred theoretical viewpoint, but more favorable when it was doctored to report results consistent with the reviewers' preferred theoretical viewpoint (49). Add to this finding that there is compelling evidence that women faculty are more likely to view gender bias as a problem within their current working academic context (40), and it is possible that women may evaluate research demonstrating a gender bias (belief consistent) more favorably than men, but evaluate research demonstrating no gender bias (belief inconsistent) less favorably than men.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…A classic empirical example of confirmation bias showed that peer-reviewers were less favorable toward an essentially identical research manuscript when it was doctored to report results inconsistent with the reviewers' preferred theoretical viewpoint, but more favorable when it was doctored to report results consistent with the reviewers' preferred theoretical viewpoint (49). Add to this finding that there is compelling evidence that women faculty are more likely to view gender bias as a problem within their current working academic context (40), and it is possible that women may evaluate research demonstrating a gender bias (belief consistent) more favorably than men, but evaluate research demonstrating no gender bias (belief inconsistent) less favorably than men.…”
mentioning
confidence: 83%
“…In fact, a recent (nonexperimental) analysis of naturally occurring online comments written by readers of popular press articles covering the research of Moss-Racusin et al (10) suggests that men were more likely than women to demonstrate negative reactions to experimental evidence of gender bias (35). Further, several lines of theorizing suggest that men may evaluate such research as less meritorious than would women (24,(36)(37)(38)(39)(40)(41)(42). Among these theories, Social Identity Theory (36)(37)(38) and related perspectives (39) posit that people are motivated to perceive their group favorably and defend that perception against threat, and that people within privileged groups often seek to retain and justify their privileged status (39).…”
mentioning
confidence: 99%
“…And in the United States, increased gender participation is argued to be essential for maintaining the US as the global scientific leader with a competitive scientific workforce (Ecklund et al, 2012). The issue of women's participation in STEM is thus of increasingly broad public policy concern.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers claim that the superior academic performance demonstrated by women in medical careers is due to their instinctive desire to help humankind. 4,6 Women have also been described as being more perceptive to emotions, enabling them to be more caring and empathetic. 6 Their enhanced academic performance may also be due to goal setting, commitment and discipline in following a structured curriculum, spending more time studying and developing stronger social networks; these attributes may develop as a result of social and cultural customs that encourage women to perform well academically.…”
mentioning
confidence: 99%